Relation Between Conductivity and Ion Content in Urban Wastewater - Le Bonté, Sébastien; Pons, Marie-Noelle; Potier, Olivier; Rocklin, Pascal (Revue des sciences de l'eau / Journal of Water Science, 2008)
AbstractWastewater conductivity has been monitored for extended periods of time by in situ probes and on grabbed samples in four communities (from 1,000 to 350,000 PE). In parallel, the concentrations of the main ionic contributors, such as calcium, sodium, potassium, magnesium, ammonium, ortho-phosphate, chloride and sulphate have been measured and their variations with respect to time compared to human activity patterns. It appears that sodium, potassium, ammonium and ortho-phosphate, which contribute to about 34% to wastewater conductivity, exhibit diurnal variations in phase with human activity evaluated by absorbance at 254 nm. However calcium (≈ 22% of wastewater conductivity) is out‑of-phase. This release, ahead of the one of other cations and anions, could be related to sewer concrete corrosion or to groundwater infiltration. The combination of these different ionic contributions creates a conductivity pattern which cannot be easily related to human activity. It makes difficult to integrate conductivity in a monitoring system able to detect ion-related abnormalities in wastewater quality.